FAKTOR–FAKTOR YANG MEMPENGARUHI CASH HOLDING PERUSAHAAN - SAUL FERNANDO SIMANJUNTAK; A. SRI WAHYUDI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this research is to test and analyze empirically the influence of profitability, firm size, net working capital, leverage and growth opportunity toward cash holding. The object of this research is property, real estate and building construction sector companies that listed in Indonesia Stock Exchange period 2009 – 2015. The technique used to sampling is purposive sampling technique where 11 companies met the criteria and were analyzed using Eviews 9 with method use is panel data regression with fixed effect model to test the hypothesis. The research finding can be summarized as follows. First, profitability has positive influence toward cash holding. Second, net working capital has negative influence toward cash holding. Finnaly firm size, leverage, and growth opportunity do not have influence toward cash holding.